Listen to yourself: The medial prefrontal cortex modulates auditory alpha power during speech preparation - Müller-Voggel, Nadia; Leske, Sabine; Hartmann, Thomas; Szebenyi, Szabolcs; Weisz, Nathan (Cerebral Cortex, 2015)
How do we process stimuli that stem from the external world and stimuli that are self-generated? In the case of voice perception it has been shown that evoked activity elicited by self-generated sounds is suppressed compared with the same sounds played-back externally. We here wanted to reveal whether neural excitability of the auditory cortex-putatively reflected in local alpha band power-is modulated already prior to speech onset, and which brain regions may mediate such a top-down preparatory response. In the left auditory cortex we show that the typical alpha suppression found when participants prepare to listen disappears when participants expect a selfspoken sound. This suggests an inhibitory adjustment of auditory cortical activity already before sound onset. As a second main finding we demonstrate that the medial prefrontal cortex, a region known for selfreferential processes, mediates these condition-specific alpha power modulations. This provides crucial insights into how higher-order regions prepare the auditory cortex for the processing of self-generated sounds. Furthermore, the mechanism outlined could provide further explanations to self-referential phenomena, such as "tickling yourself". Finally, it has implications for the so-far unsolved question of how auditory alpha power is mediated by higher-order regions in a more general sense.
Created from Fastlane, Scopus look-up
Keywords: Effective connectivity; Efference copy; MEG; Oscillation; Top-down